Increasing cumulative cabergoline dose in patients with prolactinoma improves metabolic parameters independently of decrease in prolactin levels - Demir, Ahmet Numan; Birol, Alara; Özaydın, Dilan; Şahin, Serdar; Kadıoğlu, Pınar (The European Research Journal, 2025)
Objectives: In prolactinoma patients treated with cabergoline, all of whom achieved normoprolactinemia, longitudinal changes in metabolic parameters and the factors influencing these changes were investigated. Methods: This retrospective-longitudinal study was conducted at a pituitary disease center. Medical records of newly diagnosed prolactinoma patients between 2013 and 2023 were reviewed. After applying exclusion criteria, 102 prolactinoma patients were included in the final analysis. Clinical and laboratory parameters of prolactinoma patients were recorded. Metabolic parameters assessed were fasting plasma glucose, lipid levels, fasting insulin levels, HbA1c levels, and Homeostatic Model Assessment-Insulin Resistance (HOMA-IR) levels. Subsequently, metabolic parameters assessed at the initial and final visits were compared, and factors influencing these parameters were analyzed. Results: All prolactinoma patients were treated with cabergoline, and all were in remission at their final visit. The treatment significantly reduced fasting plasma glucose, HbA1c, and LDL cholesterol levels (P<0.05). Although there were improvements in other lipid parameters, fasting insulin, BMI, and HOMA-IR compared to baseline, the differences were not statistically significant. A correlation analysis was conducted to identify factors influencing fasting plasma glucose, HbA1c, and LDL cholesterol levels at the final visit in prolactinoma patients. The analysis revealed that only the cumulative dose of cabergoline significantly impacted all three metabolic parameters (P<0.05). Conclusions: Cabergoline not only balances prolactin levels but also directly improves metabolic health. Current and future evidence clearly indicates that dopamine agonists like cabergoline could be an effective treatment not only for patients with prolactinomas but also for individuals affected by metabolic disorders without hyperprolactinemia.